The Relationship Between Ferroptosis and Diseases - Lv J; Hou B; Song J; Xu Y; Xie S (Journal of Multidisciplinary Healthcare, 2022)
Jinchang Lv, Biao Hou, Jiangang Song, Yunhua Xu, Songlin Xie Department of Hand and Foot Microsurgery, The affiliated Nanhua Hospital of University of South China, Hengyang, People’s Republic of ChinaCorrespondence: Songlin Xie, Department of Hand and Foot Microsurgery, The affiliated Nanhua Hospital of the University of South China, Hengyang, People’s Republic of China, Tel +86 13975404959, Email xiesonglin0929@163.comAbstract: Ferroptosis is an iron-dependent mode of cell death. It can occur through two major pathways, exogenous (or transporter-dependent) and endogenous (or enzyme-regulated) pathways are activated by biological or chemical inducers, and glutathione peroxidase activity is inhibited, which causes intracellular iron accumulation and lipid Peroxidation. Ferroptosis is closely related to the pathological process of many diseases. How to intervene in the occurrence and development of related diseases by regulating ferroptosis has become a hot research topic. At present, studies have shown that ferroptosis is found in common diseases such as tumors, inflammatory diseases, bacterial infections, pulmonary fibrosis, hepatitis, inflammatory bowel disease, neurodegenerative diseases, kidney injury, ischemia-reperfusion injury and skeletal muscle injury. This article reviews the characteristics and mechanism of ferroptosis, and summarizes how ferroptosis participates in the pathophysiological process in various systemic diseases of the body, which may provide new references for the treatment of clinical diseases in the future.Keywords: ferroptosis, mechanisms of ferroptosis, iron metabolism, cell death, systemic diseases